Ethel Merman : [large type] : a life - Kellow, Brian (Thorndike Press, 2008)
A biography equal to the outsized personality of one of Broadway's best-loved stars. From her breakout rendition of "I Got Rhythm" in 1930 to her triumphant performance as Gypsy's Mama Rose in 1959, Ethel Merman defined Broadway stardom for two generations of music lovers. Merman's singing voice--brassy, penetrating, and undeniably American--has transcended genre and era to become a cultural icon. As an entertainer she burned with unstoppable energy; offstage she was the original diva, a woman who knew what she wanted and brooked no interference. Her spats and zingers have become part of theater lore. In an era dominated by outsized personalities and egos, none was more vibrant and powerful than Merman's, yet beneath the tough-dame image was an enormously vulnerable and often lonely woman. Kellow's book, which includes recollections from Merman's friends, colleagues, and family members, stands as the definitive biography and an affectionate portrait of an unforgettable star.--From publisher description.